Improvement of Weakness and Pain of the Right Upper Limb Associated with Herpes Zoster Following Complex Korean Medicine Treatment: A Case Report - Hyesoo Jeon; Shin-Hyeok Park; Sohae Cho; Sol Jeong; Nam Geun Cho (MEDrang Inc., 2023)
Herein, we report the effectiveness of Korean medicine for the treatment of postherpetic upper limb weakness and pain. The patient received a combination of Korean medicine treatment modalities, including electroacupuncture, pharmacopuncture, and herbal medicine. Muscle strength and pain were evaluated using a manual muscle test (MMT) and a Numerical Rating Scale (NRS), respectively. The overall MMT score improved after hospitalization, and elbow extension improved from 3+ at admission to 5 at discharge. The NRS score improved to 2 at discharge. This study suggests the effectiveness of a combination of Korean medicine modalities in treating postherpetic motor nerve paralysis.